PENERAPAN INTERNALISASI NILAI RELIGIUS BERBASIS MODERASI BERAGAMA MELALUI PENDIDIKAN MULTIKULTURAL DI MADARSAH ALIYAH NEGERI (MAN) 1 SITUBONDO - Samsul Arifin; Qurratul A'ini (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Internalizing the religious character of religion through multicultural education at Madarsah Aliyah Negeri 1 Situbondo. It is interesting to study in relation to its environment and teachings, the Madrasah Aliyah Negeri 1 Situbondo under the auspices of the Nurul Wafa Islamic Boarding School to oblige all students to live and study religion in Islamic boarding schools. Therefore, students develop habits, and associate with them in accordance with the values ??of multicultural education, namely the value of tolerance, students can become more tolerant. Making learning in schools that can build and shape students' personalities. Religious education, discipline, tolerance, honesty, national spirit. This is done to form students with positive personality and insight